SMARTCHAIN - Towards Innovation-Driven and Smart Solutions in Short Food Supply Chains - Francisco Javier Casado Hebrard; Susanne Braun; Dimitrios Argyropoulos (International Journal of Food Studies)
In recent times, Short Food Supply Chains (SFSCs), i.e., supply chains in which the number of intermediaries between farmer and consumer are minimal or ideally nil, and local markets have flourished in Europe, both in rural and urban areas. SMARTCHAIN is a 3-year Horizon 2020 multi-actor project of 43 partners from 11 European countries, including key stakeholders from the short food supply chain domain – a kaleidoscope of ‘actors’ where science meets a wide range of non-technical disciplines and stakeholders across the agri-food value chain. Its central objective is to develop a portfolio of technological, organisational, social, and digital innovations, which will be validated in a Living Lab approach (18 pan-European use cases on short food supply chains) ensuring powerful co-creation and testing. SMARTCHAIN will develop 9 national Innovation Hubs and the SMARTCHAIN Innovation Platform, a digital portal for building a stakeholder community, and facilitating engagement, communication, and knowledge exchange across stakeholders. This special issue focuses on the most recent developments with respect to innovation in short food supply chains and publishes original research articles in this field.